TEKNIK SUPERVISOR DALAM MENINGKATKAN PROSES PEMBELAJARAN DI SEKOLAH - Nurmayuli, Nurmayuli (Lantanida Journal, 2024)
Schools still face significant challenges in their learning activities, which are impacted by a number of variables, necessitating coaching and supervision. Supervisors, who might be school heads, senior instructors, or school supervisors, are responsible for overseeing and guiding learning in schools. Finding out the methods used by supervisors in classroom instruction is the aim of this study. This study chose 17 articles which were produced using the systematic literature review study methodology, which employed analysis methodologies during the identification, screening, eligibility, and inclusion phases. The study's findings show that supervisors can improve the learning process in schools by building a harmonious relationship between supervisors and teachers, making supervision plans, preparing supervision instruments, establishing supervision techniques, carrying out supervision completely, and creating a forum for teacher development activities.